On a variational problem for a model of a Stieltjes string with a backlash at the end. (1st September 2020) - Kamenskii, Mikhail; Wen, Ching-Feng; Zvereva, Margarita
Abstract : In this paper, a model of deformations of a Stieltjes string with localized interactions with the environment (elastic supports and forces are concentrated at no more than countable set of points) is studied via variational methods. One of the boundary conditions is nonlinear and occurs due to a sleeve, which limits the movement of the right end of the string. The necessary and sufficient conditions for the extremum of the energy functional are established; the critical loads at which the contact of the end of the string with the sleeve occurs are determined; the dependence of the solution on the sleeve length is studied.